Intimate Partner Violence, Parenting, and Children’s Representations of Caregivers - Zvara, Bharathi J. (Journal of interpersonal violence, 2021)
Children’s representational models of self and relationship quality with caregivers in the context of intimate partner violence (IPV) were investigated using family drawings created by children in their first-grade year. The present study examines the mediating role of mothers’ and fathers’ sensitive parenting behaviors in the relations between IPV and children’s representations of relationship quality with mothers and fathers. The sample (N = 947) is drawn from a longitudinal study of rural poverty exploring the ways in which child, family, and contextual factors shape development over time. Results of analyses indicate significant associations between IPV, sensitive parenting, and children’s representation of relationship quality with mothers and fathers. There was a significant indirect effect from IPV on children’s representation of relationship quality with fathers through paternal parenting behaviors. The findings from this study suggest that exposure to violence may affect how children view their family relationships and that fathers’ parenting behavior is a key mediating process. Implications of the findings and directions for future study are proposed.